Cytoprotective role of chondrocyte coculturing for enhanced cartilage regeneration - Muhammad Faizan Tariq; Sumera Rashid; Aisha Tarar; Umar Sajjad; Muhammad Rauf Ahmed; Bushra Ijaz; Haiba Kaul; Noreen Latief (Penerbit Universiti Kebangsaan Malaysia, 2024)
Osteoarthritis is characterized by the progressive deterioration of articular cartilage, leading to joint pain and functional impairments. Current treatment options are limited in their ability to stimulate cartilage regeneration. Evidence suggests that the co-culture technique, involving the interplay of multiple cell types, may effectively restore damaged cartilage. This investigation assessed the regenerative impact of co-culture on osteoarthritis-affected rat knee joints. Gene expression profiling validated phenotypic and biochemical expression analysis. Compared to the control group, the co-cultivated cohorts showed elevated levels of cartilage-specific markers, such as collagen and aggrecan. Notably, the group with stress and co-cultured with normal and osteoarthritic chondrocytes (H2O2+N+OA) demonstrated significant results, including lower LDH release (15.06 ± 1.461), decreased glycosaminoglycan levels (1.551 ± 0.1487), and reduced cell death percentage (17.50 ± 3.536) compared to the H2O2 control. Safranin-O staining retention also increased (28.89 ± 2.846), indicating enhanced cartilage matrix retention. Enhanced expression of survival markers such as Bcl (0.3974 ± 0.02241) and decreased apoptotic markers like Bax (0.2961 ± 0.01199) were observed, confirming the stimulation of critical genes involved in cartilage development and matrix synthesis. These findings support the potential of co-culture technology to accelerate cartilage regeneration and offer an innovative strategy to impede osteoarthritis progression.